New fuzzy preference relations and its application in group decision making - Muhamad Naim, Nur Syibrah; Abdullah, Mohd Lazim; Che Taib, Che Mohd Imran; Md. Tap, Abu Osman (World Academy of Science, Engineering and Technology (W A S E T), 2009)
Decision making preferences to certain criteriabusually focus on positive degrees without considering the negative degrees. However, in real life situation, evaluation becomes morebcomprehensive if negative degrees are considered concurrently. Preference is expected to be more effective when considering both positive and negative degrees of preference to evaluate the best selection. Therefore, the aim of this paper is to propose the conflicting bifuzzy preference relations in group decision making by utilization of a novel score function. The onflicting bifuzzy preference relation is obtained by introducing some modifications on intuitionistic fuzzy preference relations. Releasing the intuitionistic condition by taking into account positive and negative degrees simultaneously and utilizing the novel score function are the main modifications to establish the proposed preference model. The proposed model is tested with a numerical example and proved to be simple and practical. The four-step decision model shows the efficiency of obtaining preference in group decision making.